2020
DOI: 10.1177/0022034520916400
|View full text |Cite
|
Sign up to set email alerts
|

Sdccag3 Promotes Implant Osseointegration during Experimental Hyperlipidemia

Abstract: Hyperlipidemia adversely affects bone metabolism, often resulting in compromised osseointegration and implant loss. In addition, genetic networks associated with osseointegration have been proposed. Serologically defined colon cancer antigen 3 (Sdccag3) is a novel endosomal protein that functions in actin cytoskeleton remodeling, protein trafficking and secretion, cytokinesis, and apoptosis, but its roles in the osteogenic differentiation of bone marrow mesenchymal stem cells (BMSCs) and in implant os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…After fed the animals with an atherogenic HFD, we found that both serum TC level and serum LDL‐c level in the HFD‐fed mice were increased by approximately 2–3 folds when compared with the corresponding control animals fed with the standard diet. Consistent with previous findings showing that hyperlipidemia adversely affects bone metabolism, 12–15 we observed delayed bone regeneration and inhibited bone formation in the closed mandibular bone defect region of animals fed with the HFD when compared with that of animals fed with the standard diet. Using two hyperlipidemic animal models, it has been reported that a hyperlipidemic microenvironment significantly blunted parathyroid hormone (PTH)‐induced bone anabolism 25 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…After fed the animals with an atherogenic HFD, we found that both serum TC level and serum LDL‐c level in the HFD‐fed mice were increased by approximately 2–3 folds when compared with the corresponding control animals fed with the standard diet. Consistent with previous findings showing that hyperlipidemia adversely affects bone metabolism, 12–15 we observed delayed bone regeneration and inhibited bone formation in the closed mandibular bone defect region of animals fed with the HFD when compared with that of animals fed with the standard diet. Using two hyperlipidemic animal models, it has been reported that a hyperlipidemic microenvironment significantly blunted parathyroid hormone (PTH)‐induced bone anabolism 25 .…”
Section: Discussionsupporting
confidence: 92%
“…When fed with a cholesterol‐containing HFD for 12 weeks, Apoe−/− mice, a hyperlipidemic mouse model developed on the C57BL/6 genetic background, showed an approximately 8‐fold increase in TC level, and displayed decreased cortical bone volume and inhibited bone formation 12 . Using mouse and rat models, hyperlipidemia was proved to adversely affect bone metabolism and result in compromised osseointegration, eventually leading to implant loss 13 . In addition, HFD was reported to result in larger lesions of apical periodontitis with a more severe inflammatory infiltrate or significantly accelerate the progression of periodontitis 14,15 …”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with other reported findings. For example, H. Ren and Krishanthi Gunaratnam confirmed in 2 separate studies that high-fat stimulation could inhibit the osteogenic differentiation of rat bone marrow stem cells and human osteoblasts (Gunaratnam et al 2014; Ren et al 2020). Finally, and crucially, the high-fat stimulation impaired cell skeleton arrangement, morphology, and migration and also increased the accumulation of intracellular lipids.…”
Section: Discussionmentioning
confidence: 91%
“…Besides the inconsistent findings in clinical trials, some controversies and limitations still exist in basic research. It has been reported that a high-fat diet (HFD) in Wistar rats (Ren et al 2020), C57BL/6J mice (Keuroghlian et al 2015), and New Zealand rabbits (Tekin and Toker 2019) resulted in compromised osseointegration, whereas Dundar and Yaman (2016) reported that a HFD did not decrease the bone-implant connection rate in rabbit tibias. These inconsistent findings in clinical trials, as well as controversies in basic research, show the urgent need for more comprehensive and systematical studies on the effects of hyperlipidemia on implant osseointegration.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers have injected enhancers or inhibitors locally by genetic engineering. Ren et al used microarray analysis to study the effects of hyperlipidemia on osseointegration and found that applying Sdccag3-enhancer, lncRNA-MSTRG.97162.4-enhancer and miR-193a-3p-inhibitor could boost bone formation of BMSC in vitro and improve osseointegration in vivo [60]. MiR-29a-3p-enhancer was also beneficial in implant osseointegration [61].…”
Section: Local Drugs Injectionmentioning
confidence: 99%